Recent Research Trends in Thin Film Solar Cells - Turkestani, M.K Al; Major, J D; Trehame, R E; Treharne, R E; Proskuryakov, Y Y; Durose, K (Annals of Arid Zone, 2016)
6,. brief review of the scientific status of thin film solar cells is presented, and the generic research challenges identified. A study of the control of grain size in the sublimation growth of CdTe is described in which the pressure of an ambient gas was used to control the nucleation density and hence grain size. Grain diameter varied with pressure according to D (!lm) = 0.027 (Â±a.Oll) x P (torr) + 0.90 (Â±0.31) for pressures up to 200 torr. It was found that PV devices made using large-grained CdTe increased in efficiency up to the point where the grain boundary resistances were no longer limiting. The electrical performance of CdS/ITO and CdS/Sn02 junctions were investigCltedfor both as-grown and oxygen annealed CdS surfaces. The latter induced rectification, regardless of the substrate type, this being attributed to the formation of a CdO/CdS junction. Attempts to influence the performance of CdTe/CdS devices grown on oxidized and reduced CdS are described. Key words: Solar photovoltaic, CdTe, CdS, grain boundaries.